Cryo-EM Structure and Activator Screening of Human Tryptophan Hydroxylase 2 - Kongfu Zhu; Chao Liu; Yuanzhu Gao; Jianping Lu; Daping Wang; Daping Wang; Huawei Zhang; Huawei Zhang (Frontiers Media S.A., 2022)
Human tryptophan hydroxylase 2 (TPH2) is the rate-limiting enzyme in the synthesis of serotonin. Its dysfunction has been implicated in various psychiatric disorders such as depression, autism, and bipolar disorder. TPH2 is typically decreased in stability and catalytic activity in patients; thus, screening of molecules capable of binding and stabilizing the structure of TPH2 in activated conformation is desired for drug development in mental disorder treatment. Here, we solved the 3.0 Å cryo-EM structure of the TPH2 tetramer. Then, based on the structure, we conducted allosteric site prediction and small-molecule activator screening to the obtained cavity. ZINC000068568685 was successfully selected as the best candidate with highest binding affinity. To better understand the driving forces and binding stability of the complex, we performed molecular dynamics simulation, which indicates that ZINC000068568685 has great potential to stabilize the folding of the TPH2 tetramer to facilitate its activity. The research might shed light on the development of novel drugs targeting TPH2 for the treatment of psychological disorders.